Effect of Nicotinic Acid (Niacin) on Body Weight in New Zealand White Rabbits on Atherogenic Diet - Naheed Kausar , Liaqat Ali Minhas , Khadija Qamar (Journal of Rawalpindi Medical College, 2012)
Background: To study the effect of Nicotinic acid (Niacin) on body weight in NZW rabbits on atherogenic diet. Methods: In this experimental study, forty adult male New Zealand White (NZW) rabbits were randomly assigned to four groups A, B, C and D, each comprising ten rabbits. Group A served as Pure Control and received standard animal house diet (concentrated diet). Group B as treated control was given atherogenic diet (concentrated diet + 0.5% cholesterol), Group C as an experimental group was given Niacin in a dose of 15mg/kg b.w mixed in atherogenic diet (concentrated diet + 0.5% cholesterol) for two months. Group D served as an experimental group received atherogenic diet (concentrated diet + 0.5% cholesterol) for two months then was shifted to standard animal house diet (concentrated diet) mixed with Niacin in a dose of 15mg/kg b.w. Rabbits were weighed at the beginning of the experiment and then before their sacrifice. Results: - The mean initial body weight (Wi)of rabbits in group A,B,C and D was 1.875±0.094, 1.670±0.067, 1.660±0.085 and 1.805±0.038 kg respectively. The mean final body weight(Wf) of rabbits was 1.850±0.099, 1.920±0.046, 1.695±0.069 and 1.745±0.052 kg respectively. ANOVA showed significant (p<0.05) difference in mean values of body weight among the groups. Post Hoc test using Least Significant Difference (LSD) showed significant difference (p<0.05), when weight change was compared among the groups. Conclusions: - Atherogenic diet produced increase in body weight of rabbits. Less weight gain was seen in rabbits on atherogenic diet with niacin supplementation. Marked response to reduction in body weight was observed in rabbits with cholesterol restriction and niacin supplementation